Nick Joaquin’s Cándido’s Apocalypse: Re-imagining the Gothic in a Postcolonial Philippines - Arong, Marie Rose B. (Text Matters: A Journal of Literature, Theory and Culture, 2016)
Nick Joaquin, one of the Philippines’ pillars of literature in English, is regrettably known locally for his nostalgic take on the Hispanic aspect of Philippine culture. While Joaquin did spend a great deal of time creatively exploring the Philippines’ Hispanic past, he certainly did not do so simply because of nostalgia. As recent studies have shown, Joaquin’s classic techniques that often echo the Hispanic influence on Philippine culture may also be considered as a form of resistance against both the American neocolonial influence and the nativist brand of nationalism in the 1950s and 1960s. Despite the emergence of Gothic criticism in postcolonial writing, Joaquin’s works have rarely received the attention they deserve in this critical area. In this context, this paper explores the idea of the Gothic in Joaquin’s writing and how it relates to Joaquin being the “most original voice in postcolonial Philippine writing.” In 1972, the University of Queensland Press featured Joaquin’s works in its Asian and Pacific writing series. This “new” collection, Tropical Gothic (1972), contained his significant early works published in Prose and Poems (1952) plus his novellas. This collection’s title highlights a specific aspect of Joaquin’s writing, that of his propensity to use Gothic tropes such as the blending of the real and the fantastic, or the tragic and the comic, as shown in most of the stories in the collection. In particular, I examine how his novella (Cándido’s Apocalypse) interrogates the neurosis of the nation—a disconnection from the past and its repercussions on the present/future of the Philippines.